SPE EUROPEC/EAGE Annual Conference and Exhibition 2010
DOI: 10.2118/130151-ms
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Gas Recovery, Challenges Shown at the Example of three Gas Fields

Abstract: CO 2 -EOR has been used successfully to recover incremental oil after water flooding. In the USA, more than 260,000 bbl/d are produced by using this EOR method. CO 2 Enhanced Gas Recovery (CO 2 -EGR) has also been proposed, however, only small scale projects have been performed until know.In this paper, the challenges of CO 2 -EGR are addressed at the example of three fields.The Hoeflein Field (Austria) contains gas condensate with a maximum liquid drop out of 4 %. The simulation results show that CO 2 injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The numerical simulation study results showed that the best development effect was achieved when the injection well was located on the side of the structure. The recovery could be increased to about 1.6%, but the output resulted in about 32% CO 2 [15].…”
Section: Examples Of Gas Injection Egr Researchmentioning
confidence: 98%
See 2 more Smart Citations
“…The numerical simulation study results showed that the best development effect was achieved when the injection well was located on the side of the structure. The recovery could be increased to about 1.6%, but the output resulted in about 32% CO 2 [15].…”
Section: Examples Of Gas Injection Egr Researchmentioning
confidence: 98%
“…However, these technologies still have limitations; so, the gas injection method has been developed. By injecting CO 2 , N 2 and their mixtures, recovery efficiency in gas reservoirs can be effectively enhanced, and the long-term stable production of gas fields can be supported [15]. Specifically, CO 2 injection can not only help to enhance gas recovery but also allow for the capture and storage of CO 2 to deal with the current greenhouse effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its efficiency is highly dependent on reservoir type, temperature and pressure conditions, heterogeneity, production strategy, and so on [55][56][57][58][59][60]. For some CO 2 -EGR projects, the gas recovered can reach 10%, while other projects have seen less or no enhancement [61][62][63]. The rapid breakthrough of CO 2 in a production well, resulting in a high concentration of CO 2 , restricts the production of pure natural gas [64].…”
Section: Ccus: Co 2 -Egrmentioning
confidence: 99%
“…The literature tends to focus either on maximising incremental production or on CO 2 storage capacity. However, simultaneous enhanced gas recovery (EGR), enhanced condensate recovery (ECR) and CO 2 storage may be feasible (Oldenburg, 2003;Oldenburg et al, 2004;Ramharack et al, 2010;Clemens et al, 2010). Following the European Trading Scheme, commercialising simultaneous EGR, EGR and CO 2 storage for all gas reservoirs is now being considered.…”
mentioning
confidence: 99%